ANALISIS KOMPARATIVE CASH RATIO DAN DEBT TO ASSETS RATIO TERHADAP RETURN ON ASSETS PADA PERUSAHAAN RETAIL TRADE DAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nasyaroeka, Jhon (Jurnal Manajemen Magister Darmajaya, 2016)
This research to determine the independent variable that is variable cash rasio and debt to assets rasio as well as the return on assets as the dependent variable on two company that the company retail trade and Telecommunication company has influence with the simultaneously,through the test F. And this reseach no difference in the influence of simultaneously or the same of independent variable with the dependent variable. Â Keyword : Cash Rasio,Debt to Assets Rasio,Return on Assets,The Test F/Simultan test.Â